Two Tetrahymena kinesin-9 family members exhibit slow plus-end-directed motility in vitro - Hiroto Ishii; Masahiko Yamagishi; Junichiro Yajima (Scientific Reports, 2024)
Abstract The kinesin-9 family comprises two subfamilies specific to ciliated eukaryotic cells, and has recently attracted considerable attention because of its importance in ciliary bending and formation. However, only scattered data are available on the motor properties of kinesin-9 family members; these properties have not been compared under identical experimental conditions using kinesin-9 motors from the same species. Here, we report the comprehensive motor properties of two kinesin-9 molecules of Tetrahymena thermophila, TtK9A (Kif9/Klp1 ortholog) and TtK9B1 (Kif6 ortholog), using microtubule-based in vitro assays, including single-motor and multi-motor assays and microtubule-stimulated ATPase assays. Both subfamilies exhibit microtubule plus-end-directed, extremely slow motor activity, both in single and multiple molecules. TtK9A shows lower processivity than TtK9B1. Our findings indicate that the considerable slow movement of kinesin-9 that corresponds to low ATP hydrolysis rates is a common feature of the ciliary kinesin-9 family.